O perdão de Deus : um análise sobre a angústia de culpa e a idealização do eu em Lucas 15.11-32 a partir da compreensão de paternidade na perspectiva teológica e psicanalítica - Armange, Marcos Augusto (2007)
The goal of this work is to analyze the human existential conflict that appears in the tension between the demands of an absolutized authority (Law) found in the psychoanalytic view and in the theological view in the representation of the father, superego, God and the sin as a theological and anthropological category, as a condition of every existence, and at the same time a voluntary act that makes it impossible to meet the legal expectations of a demanding authority. It highlights the classical manifestations of this conflict: the feeling of gilt, understood here as anguish of gilt, of the one who cannot meet the demands; and the pride understood as the idealization of the self, of the one who understands himself or herself as a person able to meet the expectations of the authority. Gilt and pride are factors of destruction of the human being according to the theological and psychoanalytic perspectives. In order to solve this conflict it wants to examine the image of Father that Jesus presents in his relationship with God. It understands that this representation, originated in forgiveness, is a paradigm in the relativization of the absolutized figure, in the surpassing of sin, for the notion of a new justice, for the healing of gilt and for a real image of the human being not based on pride.